HAK ATAS INFORMASI TERHADAP BAHAN KOSMETIK PENGGUNA JASA KLINIK KECANTIKAN BERDASARKAN UNDANG – UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN: Jihan Nur Rahmah - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2019)
Consumers have the right to information on the goods they consume, but in practice beauty clinic services are still commonly found to violate the UUPK rules, namely not fulfilling the right to consumer information on cosmetic ingredients used. The problem is how the fulfillment of the right to information on cosmetic ingredients and how to resolve disputes over violations by Beauty Clinic Services that do not supplement information on beauty products. The purpose is to obtain information on the implementation of fulfilling the right to information on cosmetic ingredients and dispute resolution for violations committed by Beauty Clinic Services that do not supplement information on beauty products. Its usefulness is to provide information on the implementation of the fulfillment of the right to information on cosmetic ingredients and dispute resolution for violations by Beauty Clinic Services that do not supplement information on beauty products. The research method used is normative juridical. From the results of the study found that there are still many clinics that have not fulfilled their obligations as a business actor where the right to information on the cosmetic ingredients that are not fulfilled is fulfilled. Dispute resolution can be done outside and in court. Where outside the court is carried out by means of mediation between consumers and business actors, it can also be done by way of consolidation and arbitration. Furthermore, if it is not resolved, it can be reached through a court which is regulated in article 45 of the UUPK. The conclusion is that there are still many beauty clinic services that do not provide information rights to the ingredients contained in cosmetics and dispute resolution for violations committed by Beauty Clinic Services for information that is not equipped with consumer disputes can be reached through the court or outside the court based on the voluntary choice of the parties the disputes